Global Attractivity of Positive Periodic Solution for a Delayed Predator-Prey System with Diffusion and Impulses - Yuanfu Shao; Xiaolan Xie; Zhixiang Ju (Journal of Applied Mathematics)
By constructing a suitable Lyapunov functional, the global attractivity of positive periodic solutions for a delayed predator-prey system with diffusion and impulses is studied in this paper. Finally, an example and numerical analysis are given to show the effectiveness of the main results.